Abiotic factors controlling the seasonal and spatial patterns of phytoplankton community in the Tigris River, Turkey - Varol, M.; Sen, B. (Wiley, 2018)
In this study, the seasonal and spatial dynamics of the phytoplankton community in the Tigris River (Turkey) and the relationships with environmental factors were analysed. Bacillariophyta were the most important taxonomic group both in terms of abundance and species number. Phytoplankton abundance increased from winter to autumn associated with a decline in discharge and an increase in nutrient concentrations and water temperature. There was a downstream increase in phytoplankton abundance and species number in the river. Similar spatial and seasonal patterns were observed in chlorophyll-a concentration and phytoplankton abundance. Redundancy analysis and correlation analysis revealed that chemical variables, mainly nutrients were the most important abiotic factors controlling phytoplankton abundance in the Tigris River.
Keywords: abiotic factors; chlorophyll-a; phytoplankton; redundancy analysis; Tigris River